2018
DOI: 10.22336/rjo.2018.6
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between internal and external ocular factors and macular pigment optical density

Abstract: Aim. To assess the relationship between the macular pigment optical density and blue-light issued by computers, glare sensibility, with iris color, age, sex, or refractive errors. Material and methods. 83 patients (166 eyes) were enrolled in a prospective observational study. They were divided into 2 groups: group 1 (study group) - computer using patients (time spent in front of the computer for minimum 8 hours per day, 5 days per week, 2 years) - 43 patients and group 2 (control group) - 40 patients. The foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…The mean MPOD in the current study was 0.59. This value was comparable to those measured using the HFP technique for young to middle-aged healthy individuals in our previous studies (0.67 [17] and 0.65 [16]) and other studies using other techniques (0.47 to 0.72 [35][36][37]).…”
Section: Discussionsupporting
confidence: 90%
“…The mean MPOD in the current study was 0.59. This value was comparable to those measured using the HFP technique for young to middle-aged healthy individuals in our previous studies (0.67 [17] and 0.65 [16]) and other studies using other techniques (0.47 to 0.72 [35][36][37]).…”
Section: Discussionsupporting
confidence: 90%
“…Some studies did record BMI, because BMI would affect the concentration of lutein in serum [58], which was found not to differ significantly between patients who received supplementation or not. One study suggested that iris color affects MPOD, but another showed no such relationship [59]. Iris color was not recorded in studies included in this meta-analysis and therefore could not be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two publications met the inclusion criteria (Table 1, Fig. 1, Supplementary Table 2) [11,12,14,16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Fifteen studies were conducted in the USA, three in Ireland, one in England, one in Spain, one in Romania, and one did not clearly specify the country.…”
Section: Resultsmentioning
confidence: 99%